Retratos, imagens, letras e numeros colados nas paredes:representaçãoes sociais de escola para ribeirinhos dos rios Môa e Azul - Acre - Lima, Maria Aldecy Rodrigues de (2008)
Remote Communities. Absence of artifacts and minimization of the exacerbated consumption of modernity. The desire which spread beyond what reality can provide. Expressions like this are present in this paper which focus in the social representations of school built by residents who live at the riversides of Môa and Azul Rivers, in Mâncio Lima, Acre State. To do so, we used the methodological contribution of the semi-structured interview, observation of the place while a natural inhabitant of the region, and also photos analyses of local reality. A key feature of the riverside homes is the glued paper on the walls of houses forming a panel set of portraits, pictures, letters and numbers for all appreciated. Regardless of whether or not read, there is admiration for the color of the images, the layout of the letters, and the things of the city awakening the desire to obtain school knowledge. The resident of this Amazon region maintains a close relationship between thinking, acting and feeling living harmonically with nature that connects them to the ideal landscape which is revisited by the graphic material that attracts wondering what exists beyond the shores of the river, beyond the horizon of green forests. It is a life entirely accomplished by the imaginary where exist a framed landscape merged and confused by the real and the supernatural, in which men and gods walk together by the forest, sailing by the rivers and seek a possible aesthetic between the real and ideal. The Theory of Social Representations spread by Serge Moscovici (2005) and Jodelet (2001) guided our gaze on the understanding what the school is and its representation to the riversides, as well to reveal the relation they practice with the knowledge that is spread by the mystification and the knowledge that is practice daily. Based in Bardin s thematic analysis (2004) we tried to raise such contents combining them in five analysis categories